Supracricoid partial laryngectomy and reconstruction of the anterior epiglottic space flap: a new surgical approach for supracricoid partial laryngectomy - Mao, Chenggang; He, Zhiqun; Liu, Linglong; Zhang, Yi; Chen, Fei; Liang, Xi (Frontiers in Oncology, 2025)
ObjectiveTo introduce a novel surgical technique for partial laryngectomy involving the reconstruction of the epiglottic space flap (ESFR) on the cricoid cartilage, and to compare its clinical efficacy and functional outcomes with those of cricohyoidoepiglottopexy (CHEP) in the treatment of laryngeal squamous cell carcinoma, exploring the feasibility and clinical significance of this new surgical approach.MethodsA retrospective analysis was conducted on 57 patients with laryngeal squamous cell carcinoma who were treated between January 2014 and January 2020. The inclusion criteria were suitability for CHEP according to the 2002 UICC criteria and the absence of anterior epiglottic space invasion. Postoperative complications, glottic area status, recurrence, and survival were compared between the CHEP group (n=22) and the ESFR group (n=35).ResultsFollow-up (44-116 months; 94.7% rate) revealed similar 3-year (CHEP: 90.6%; ESFR: 91.5%; P>0.05) and 5-year (CHEP: 83.3%; ESFR: 89.3%; P>0.05) cumulative survival. ESFR significantly reduced extubation time (ESFR: 8 ± 2.5 days; CHEP: 18 ± 3.1 days; P<0.01) and swallowing errors (ESFR: 5.7%; CHEP: 22.7%; P<0.05). No significant differences were observed in pharyngeal fistula, laryngeal stenosis, or recurrence rates (P>0.05).ConclusionCompared to CHEP, ESFR technique demonstrates equivalent surgical eligibility criteria and oncological resection margins. However, ESFR uniquely preserves the anatomical integrity of the laryngeal framework, enabling superior postoperative functional outcomes through expedited restoration of phonatory and deglutitive capacities while maintaining long-term laryngeal preservation.